THE EFFECT OF SOCIAL MEDIA AS A MARKETING TOOL ON CUSTOMERS’ PURCHASE DECISION FOR LOCAL BRANDS - Ishak Bin Abd Rahman; Abdullah Sanusi Othman; Abdullah Sanusi Othman; Lokhman Hakim Osman; Azmi Bin Aziz (Journal of Islamic, Social, Economics and Development, 2023)
The value of social media marketing has grown since the COVID-19 pandemic began. Many businesses implement social media to influence consumer purchase decisions and reach new consumers. The increased use of social media has given marketers a better platform to communicate with customers. However, research on the influence of social media marketing on branding has been relatively unexplored. The purpose of this research is to investigate the effect of social media as a marketing tool based on four elements of social media marketing influence on customer purchase decisions for local brands. Data were collected online using Google Form from 188 social media users in eight provinces in Indonesia. Multiple linear regression analysis was used to examine the postulated research model. The findings found brand awareness, electronic word of mouth, social media usage, and interaction influence purchase decision for local brands. Therefore, social media was proven as a marketing tool, and marketers can use social media platforms to influence customers’ purchase decisions.